Exercise-induced adaptations of rat soleus muscle grafts - White, Timothy P.; Villanacci, John F.; Morales, Pedro G.; Segal, Steven S.; Essig, David A. (University of Michigan, 1983)
In female Wistar rats (n = 316) under pentobarbital sodium anesthesia, the soleus muscle was autografted with its nerve reimplanted. One purpose was to characterize the chronological development of graft innervation and recruitment during locomotion. Furthermore, we tested hypotheses regarding the efficacy of run conditioning of different intensities, durations, and postgrafting initiation times to alter mass and pyruvate-malate oxidation capacity of grafts. Choline acetyltransferase activity of grafts increased from 10% of control value at 7 days postgrafting to 55 and 100% at days 28 and 56, respectively. Running-induced glycogen depletion occurred in grafts; this is consistent with graft recruitment during locomotion. There was a threshold of conditioning intensity below which no improvements occurred and above which there were improvements. Spring (50 m/min) and endurance (30 m/min) conditioning of a duration of at least 28 days that was initiated at 28 or 56 days postgrafting increased mass of grafts by 30% compared with grafts from nonconditioned rats. Easy conditioning (15 m/min) had no effect on graft mass. Changes in graft total protein content paralleled those of mass. Oxidation capacity of grafts increased significantly with some conditioning protocols, but not to the same extent as mass. The exercise-induced adaptations should improve graft function in the host organism.